Use of essential oils as natural preservatives in the meat industry: Agroindustria - Enríquez Estrella, Miguel Ángel (2025)
Essential oils, due to their antimicrobial, antioxidant, and organoleptic properties, are presented as a natural alternative to synthetic preservatives in the food industry. The objective of this study was to conduct a documentary review on the use of essential oils as natural preservatives in the meat industry. To achieve this, the SALSA method modified by Gunnarsdottir was employed, which includes an exhaustive search, critical evaluation, synthesis, and analysis of the literature, complemented by the snowball technique. The results revealed 21 essential oils derived from various plants, which exhibit antioxidant, antimicrobial, and preservative properties. These characteristics position them as key resources in the preservation of meat products, with doses ranging from 0.5 to 2 mL·kg-1 of oil, depending on the species used. In conclusion, it was determined that essential oils are effective in optimizing the quality, safety, and shelf life of meat products and their derivatives, establishing them as a valuable tool in the industry.